Pengembangan Sistem Pengelolaan Sampah Berbasis Cloud Computing SAAS untuk Optimalisasi Pengelolaan Lingkungan Berkelanjutan - Muhammad Arifin; Eko Darmnato; Esti Wijayanti; Heru Sabputro (Universitas Muria Kudus, 2025)
Waste management problems continue to increase along with population growth and urbanization, which have negative impacts on the environment and public health. Waste management is a major challenge in creating a sustainable environment. Digital-based technologies, such as Cloud Computing with a Multi-tenant SaaS (Software as a Service) model, offer solutions to overcome challenges in waste management efficiently and integrated. This technology enables real-time waste management with higher efficiency, and can be accessed by various parties, including the government, managers and the community. This study aims to develop a digital-based waste management system that utilizes Cloud Computing SaaS Multi-tenant technology for the waste management process. The research method used is the Agile-based system development method, where the research stages include needs analysis, system design, implementation, and evaluation. The results of this study include increased operational efficiency of waste management, cost savings, and increased community participation in waste management programs through an easily accessible digital platform. In addition, this research also supports sustainable development (SDGs), particularly in efforts to maintain environmental sustainability.